Penerapan Biopori untuk Menabung Air Hujan dan Pengelolaan Sampah Organik di Desa Bancer Kecamatan Ngraho Kabupaten Bojonegoro - Trifandha, Siskha; Farahdiansari, Ardana Putri; Febriansa, Nungki Dio; Utomo, Izza Ahmad (Unri Conference Series: Community Engagement, 2024)
The people of Bancer Village, Ngraho District's awareness of taking rainwater for groundwater availability has begun to decrease. This is because groundwater extraction is not accompanied by the spirit of maintenance and the lack of rainwater entering the soil. In addition, there is a problem with the lack of knowledge of housewives in waste sorting. The community's handling of organic and inorganic waste has not been the best solution. So, there needs to be conventional, systematic, and structured handling. This activity aims to help the people of Bancer Village, Ngraho District overcome water and waste problems, by socializing the importance of saving water and waste management with simple and cheap technology. The application of this biopore technology is by making biopore holes for rainwater infiltration into the soil so that it can maintain the limitations of composter groundwater and overcome the problem of organic waste in Bancer Village. Biopore holes are useful as a place to absorb water into the soil and as a place to make compost from household waste. This biopore hole does not require a large amount of land so it can be the right solution to water and waste problems in Bancer Village. The result of the activity is the installation of 6 biopore infiltration holes as an example to be used and developed by the community.